Lipase-Catalyzed Synthesis of Sn-2 Palmitate: A Review - Wei Wei; Cong Sun; Xiaosan Wang; Qingzhe Jin; Xuebing Xu; Casimir C. Akoh; Xingguo Wang (Engineering, 2020)
Human milk fat (HMF) is an important source of nutrients and energy for infants. Triacylglycerols (TAGs) account for about 98% of HMF and have a unique molecular structure. HMF is highly enriched in palmitic acid (PA) at the sn-2 position of the glycerol backbone (more than 70%) and in unsaturated fatty acids at the sn-1,3 position. The specific TAG structure in HMF plays a valuable function in infant growth. Sn-2 palmitate (mainly 1,3-dioleoyl-2-palmitoyl-glycerol) is one of the structured TAGs that is commonly supplemented into infant formula in order to enable it to present a similar structure to HMF. In this review, the development of the lipase-catalyzed synthesis of sn-2 palmitate over the last 25 years are summarized, with a focus on reaction schemes in a laboratory setting. Particular attention is also paid to the commercialized sn-1,3 regioselective lipases that are used in structured TAGs synthesis, to general methods of TAG analysis, and to successfully developed sn-2 palmitate products on the market. Prospects for the lipase-catalyzed synthesis of sn-2 palmitate are discussed.